Euthanasia Dalam Tinjauan Aspek Hak Asasi Manusia - tri susilowati (Justicia Journal, 2016)
With the development in the field of medicine, is not impossible to contain the thorny and complex issue which through knowledge and medical technology is very current, diagnosis of a disease can be more perfect, more immediate treatment can penyakitpun eefektif. With modern medical equipment, then the pain a person can diperingann seseorangpun life can be extended for a certain period of time by installing a "Respirator", even when the calculation of a person's death disease patients can be more precise.The problems that arise from such diverse medical technology advances, one of them is euthanasia. Euthanasia means the act, ending the life of someone who according to medical science will not sembuhlagi, or death actively facilitate actions, whether conducted by delivering pain medication overdose or with the tools necessary in maintaining the patient's life.Sedanglkan Passive euthanasia is given as an act of medical termination of patient effort. Of the two types of euthanasia mentioned above, in terms of Indonesian positive law was contrary to the 1945 Constitution, if the terms of Human Rights (HAM) is also contradictory premises n nature ofGodAlmighty.